Thermal Analysis of Air-cooled Enclosed PMSM Based on Thermal Network - Wu Jiangquan; Liang Jinxue; Yang Jinxia; Li Huaxiang; Chen Zhichu (机车电传动)
For the high power density and poor heat dissipation condition, much attention was paid on thermal design of air-cooledenclosed PMSM. The application of the thermal network method in the analysis of temperature rise of PMSM was investigated. A thermalnetwork model was presented for a certain PMSM, and its thermal parameters were calculated based on MATLAB/SIMULINK. With thethermal network, rapid calculation of thermal performance of PMSM could be achieved. Compared with experimental results, the thermalnetwork proved higher accurate for design, and had guiding significance to the thermal design of PMSM.